2019
DOI: 10.35188/unu-wider/2019/668-5
|View full text |Cite
|
Sign up to set email alerts
|

The wage-setting power of firms: Rent-sharing and monopsony in South Africa

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…I estimate here that nearly half of the gender wage gap is accounted for by net differences in firm average wages as opposed to net differences in the own-wage gap. This is consistent with my previous analysis in Bassier (2019), where I similarly estimated that nearly half of the gender wage gap is accounted for by differences in the types of firms women are at compared to men (as measured by AKM firm wage premia).…”
Section: Description Of the Matched Panelsupporting
confidence: 90%
See 1 more Smart Citation
“…I estimate here that nearly half of the gender wage gap is accounted for by net differences in firm average wages as opposed to net differences in the own-wage gap. This is consistent with my previous analysis in Bassier (2019), where I similarly estimated that nearly half of the gender wage gap is accounted for by differences in the types of firms women are at compared to men (as measured by AKM firm wage premia).…”
Section: Description Of the Matched Panelsupporting
confidence: 90%
“…Average separations decrease by about 2 per cent at the event year (statistically significant in event years 0 and 1), after flat pretrends. Interpreted directly, this implies a firm labour supply elasticity of about 1.5, which suggests considerable monopsony power in line with Bassier (2019). 10 However, this is very likely biased as an estimate of a reduction in turnover since I cannot differentiate between voluntary quits and involuntary fires.…”
Section: Resultsmentioning
confidence: 99%
“…I interrogate this implausible result in the context of earnings imputation in the QLFS below. Bassier (2019) undertook a brief comparison of some percentiles in the IRP5 data and the household surveys in PALMS and found that they roughly corresponded (Bassier 2019: 5). I undertake a more thorough comparison in the analysis in this paper.…”
Section: Tax Data and Inequalitymentioning
confidence: 99%
“…As I describe in more detail below, matched firm and worker data for South Africa from SARS, similar to the data used by Song et al (2019) and Alvarez et al (2018), was recently made available to researchers through a project between SARS, the South African National Treasury, and UNU-WIDER. Bassier (2019) used this data and a decomposition from Abowd et al (1999) to document that firm wage premia accounted for 25 per cent of the variance of workers' wages. Bhorat et al (2017) undertook a similar decomposition and found this to be 13 per cent.…”
Section: Earnings Inequality and Firmsmentioning
confidence: 99%
“…3 There have only been a handful of research papers that have used these data in the past five years. The research has mostly covered job flows (Kerr 2018), the employment tax incentive (Chatterjee and Mcleod 2016;Ebrahim and Pirttilä 2019;Ebrahim et al 2017), and wage inequality among employees (Bassier 2019;).…”
Section: Introductionmentioning
confidence: 99%